Development and conception of versatile agricultural machine. (2021) - Jeyakumar, R.; Ramachandran, N.; Ajay Aravind, J.; Ajithkumar, M.; Arun Kumar, K.; Dhivakar, M.
Abstract: The agriculture segment is one of the key regions to distinguish the quantity of utilizations for work using obsolete resources. Our project relates to seed fodder, pesticides and multipurpose farming machinery for fertilizers and dumping, giving the farmer the most economical and multi-use tools that are clean, easy to maintain, effortless to handle and don't require direct fuel, thus reducing costs and helping farmers in their fields. This machine uses the power of the tractor to carry out all agricultural operations. Mechanization employs the utilization of a hybrid machine between the source of power and the work. The project uses power take off wire to transmit power from the tractor to the multipurpose machine. This power extends to all the necessary processes such as sowing, watering, spraying, plowing and cutting.